Executive Compensation and Short-Termist Behaviour in Speculative Markets - BOLTON, PATRICK; SCHEINKMAN, JOSE; XIONG, WEI (Review of Economic Studies, 2006)
We present a multiperiod agency model of stock-based executive compensation in a speculative stock market, where investors have heterogeneous beliefs and stock prices may deviate from underlying fundamentals and include a speculative option component. This component arises from the option to sell the stock in the future to potentially overoptimistic investors. We show that optimal compensation contracts may emphasize short-term stock performance, at the expense of long-run fundamental value, as an incentive to induce managers to pursue actions which increase the speculative component in the stock price. Our model provides a different perspective on the recent corporate crisis than the “rent extraction view” of executive compensation.